The Effect of Leverage, Profitability, and Company Age on Audit Delay in Food and Beverages Subsector Companies Listed on the IDX in 2021-2024 - Mirnawati; Erna Puspita; Amin Tohari (Jurnal Aghniya, 2025)
The purpose of this study is to examine how audit delays in food and beverage subsector firms listed on the Indonesia Stock Exchange for the years 2021–2024 are impacted by debt, profitability, and company age. This work uses binary logistic regression analysis in a causal quantitative manner. 44 firms made up the final sample, which was chosen by purposive sampling based on the criteria of businesses that regularly released audited financial statements during the research period. The analysis's findings indicate that audit delay is not significantly impacted by leverage, profitability, or firm age. This study is interesting since it focuses on a particular sector and reveals that internal financial issues are not the primary cause of audit delays. These results emphasize how crucial it is to take into account additional factors, such as auditor caliber, corporate governance, and information technology use, in order to gain a more thorough understanding of audit delays and to encourage future improvements to audit procedures.a